2011
DOI: 10.1016/j.jip.2011.05.018
|View full text |Cite
|
Sign up to set email alerts
|

Compatibility among entomopathogenic hyphocreales and two beneficial insects used to control Trialeurodes vaporariorum (Hemiptera: Aleurodidae) in Mediterranean greenhouses

Abstract: The effect of the combined use of Encarsia formosa or Macrolophus caliginosus and one of three marketed mycoinsecticides, Mycotal® (Leucanicillium muscarium-based), Naturalis-L™ (Beauveria bassiana-based) and PreFeRal® (Isaria fumosorosea-based), on the control of the whitefly, Trialeurodes vaporariorum, was studied under laboratory and greenhouse conditions. The results of both types of tests, the bioassays and the greenhouse trials, for all combinations of E. Formosa with each of the three mycoinsecticides s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 25 publications
(36 reference statements)
0
6
0
3
Order By: Relevance
“…However, killing effect of EPF is likely to vary significantly depending on the type of arthropod natural enemy. For example, greenhouse studies with predatory mirid bugs (Hemiptera: Miridae) showed that there were no negative effects of two commercial isolates of B. bassiana (GHA and ATCC 74040) on predator populations (Labbé et al, 2009;Hamdi et al, 2011). On the contrary, densities of predatory Orius (Hem.…”
Section: Compability Of Entomopathogenic Fungi With Natural Enemiesmentioning
confidence: 99%
See 1 more Smart Citation
“…However, killing effect of EPF is likely to vary significantly depending on the type of arthropod natural enemy. For example, greenhouse studies with predatory mirid bugs (Hemiptera: Miridae) showed that there were no negative effects of two commercial isolates of B. bassiana (GHA and ATCC 74040) on predator populations (Labbé et al, 2009;Hamdi et al, 2011). On the contrary, densities of predatory Orius (Hem.…”
Section: Compability Of Entomopathogenic Fungi With Natural Enemiesmentioning
confidence: 99%
“…: Anthocoridae) species were significantly reduced due to infection by the GHA isolate of B. bassiana (Shipp et al, 2012), although in other studies there were no or only weak side effects on Orius spp. (Hamdi et al, 2011;Pourian et al, 2011). Predatory mites are generally not susceptible to commercial isolates of the entomopathogenic fungi B. bassiana, M. brunneum and I. fumosorosae both in laboratory and greenhouse trials (Ludwig & Oetting, 2001;Vergel et al, 2011;Wu et al, 2014).…”
Section: Compability Of Entomopathogenic Fungi With Natural Enemiesmentioning
confidence: 99%
“…Maia et al (2000) mencionaron que cuando los hongos entomopatógenos entran en contacto con depredadores, se pueden presentar alteraciones como inviabilidad de huevos, alteración del ciclo de vida y disminución de la capacidad de depredación; esto ocurre porque los depredadores pueden ser, al igual que la plaga, afectados directamente por los hongos entomopatógenos. Hamdi et al (2011) consideran que, a pesar de los estudios realizados aún falta información de laboratorio y campo sobre la susceptibilidad de depredadores hacia hongos entomopatógenos usados en programas de control biológico de plagas.…”
Section: Introductionunclassified
“…La mosca blanca de los invernaderos T. vaporariorum Westwood (Hemiptera: Aleyrodidae), es una especie cosmopolita y polífaga (Van Lenteren y Noldus, 1990y Hamdi et al, 2011 que ocasiona daños económicos a los cultivos al alimentarse de la savia, afectando la calidad de la planta y contribuyendo a la formación de fumagina y la transmisión de enfermedades virales (Byrne y Bellows, 1991;Van Lenteren et al, 1996;Park et al, 1998;Bi et al, 2002;Cardona et al, 2005;Arnó et al, 2006y Hamdi et al, 2011. Para el control de esta plaga los productores utilizan insecticidas sintéticos en grandes volúmenes sin cumplir los periodos de carencia, ocasionando residuos tóxicos en los frutos, desarrollo de poblaciones resistentes a los productos, destrucción de organismos benéficos, intoxicación de mamíferos y contaminación del medio ambiente (Fragoso et al, 2002;Isman, 2006;Picanço et al, 2007).…”
Section: Introductionunclassified
“…Una alternativa viable a los problemas ocasionados por el uso excesivo de insecticidas de síntesis química es la utilización de métodos de control que deben priorizar la seguridad ambiental y social y que sean eficientes en el control de T. vaporariorum. En la búsqueda de tales métodos, productos alternativos a los plaguicidas convencionales como los extractos vegetales, han sido utilizado por productores de hortalizas para el control de plagas y enfermedades (Van Lenteren et al, 1996;Simmonds et al, 2002;Choi et al, 2003;Fraser, 2005;Regnault-Roger et al, 2005;Pavela y Herda, 2007;Schuster et al, 2009;Hamdi et al, 2011;Moreau e Isman, 2012).…”
Section: Introductionunclassified